Field notes contributed by Thomas H. Kent, winter 1979-1980 - Kent, Thomas H. (Thomas Hugh), 1934-et al (1979)
List of birds and locations contributed by Thomas H. Kent with observers Thomas K. Shires, Michael C. Newlon and Cal and Bernie Knight. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of winter 1979-1980. Epson - sheet feed/flatbed